Delamination growth analysis of composite panels - Wagner, Werner; Gruttmann, Friedrich (European Journal of Computational Mechanics, 2004)
The present paper deals with the numerical simulation of delamination in composite panels. Within our model interface layers are positioned at layer boundaries where damage is expected. The material model considering inelastic strains is written in terms of the Green– Lagrangian strains and work–conjugated 2ndPiola Kirchhoff stress tensor. The delamination criterion of Hashin is reformulated as a yield criterion with softening. The critical energy release rate controls the delamination process. Refined hexahedral elements are used to discretize laminated structures. To avoid mesh dependent solutions a special regularization technique is applied. Additional viscous strain rates are superposed onto the rate independent model. Parameter studies show the influence of the different constitutive and numerical quantities. Furthermore we investigate the influence of delamination on the stability of composite plates.